Dynamic electrophysiological mechanism in patients with long-standing persistent atrial fibrillation - Osorio-Jaramillo, Emilio; Cox, James L.; Klenk, Sarah; Kaider, Alexandra; Angleitner, Philipp; Werner, Paul; Strassl, Andreas; Mach, Markus; Laufer, Guenther; Ehrlich, Marek P.; Ad, Niv (Frontiers in Cardiovascular Medicine, 2022)
Background Improved understanding of the mechanisms that sustain persistent and long-standing persistent atrial fibrillation (LSpAF) is essential for providing better ablation solutions. The findings of traditional catheter-based electrophysiological studies can be impacted by the sedation required for these procedures. This is not required in non-invasive body-surface mapping (ECGI). ECGI allows for multiple mappings in the same patient at different times. This would expose potential electrophysiological changes over time, such as the location and stability of extra-pulmonary vein drivers and activation patterns in sustained AF. Materials and methods In this electrophysiological study, 10 open-heart surgery candidates with LSpAF, without previous ablation procedures (6 male, median age 73 years), were mapped on two occasions with a median interval of 11 days (IQR: 8–19) between mappings. Bi-atrial epicardial activation sequences were acquired using ECGI (CardioInsight™, Minneapolis, MN, United States). Results Bi-atrial electrophysiological abnormalities were documented in all 20 mappings. Interestingly, the anatomic location of focal and rotor activities changed between the mappings in all patients [100% showed changes, 95%CI (69.2–100%), p < 0.001]. Neither AF driver type nor their number varied significantly between the mappings in any patient (median total number of focal activities 8 (IQR: 1–16) versus 6 (IQR: 2–12), p = 0.68; median total number of rotor activities 48 (IQR: 44–67) versus 55 (IQR: 44–61), p = 0.30). However, individual zones showed a high number of quantitative changes (increase/decrease) of driver activity. Most changes of focal activity were found in the left atrial appendage, the region of the left lower pulmonary vein and the right atrial appendage. Most changes in rotor activity were found also at the left lower pulmonary vein region, the upper half of the right atrium and the right atrial appendage. Conclusion This clinical study documented that driver location and activation patterns in patients with LSpAF changes constantly. Furthermore, bi-atrial pathophysiology was demonstrated, which underscores the importance of treating both atria in LSpAF and the significant role that arrhythmogenic drivers outside the pulmonary veins seem to have in maintaining this complex arrhythmia.